Legal Regulation of Environmental Impact Assessment in Ukraine: Current State - Nazar Shparyk (Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the main provisions of the new Law of Ukraine "On Environmental Impact Assessment". The terminology, procedure and mechanisms for environmental impact assessment are described. The possible problems that the parties will face in practice undergoing an environmental impact assessment procedure are reflected. The advantages and disadvantages of the new Law are highlighted and possible problems in the implementation of the norms of the Law are analyzed.